Incidental White Matter Lesions in Children Presentıng With Headache. Issue 6 (1st April 2013) - Bayram, Erhan; Topcu, Yasemin; Karaoglu, Pakize; Yis, Uluc; Guleryuz, Handan Cakmakci; Kurul, Semra Hiz
Abstract : Aim: We aimed to describe the prevalence and significance of white matter lesions detected on magnetic resonance imaging (MRI) in children with headache. Material and Methods: Children who were admitted with the complaint of headache and had neuroimaging between December 2007 and June 2012 were included in the study. The clinical and neuroimaging data of the patients were retrospectively evaluated. MRI results of the patients were documented in detail. The patients with non‐specific white matter lesions were called for a control visit, and current status of headache and neurological findings were determined. Results: A total of 941 patients were included in the study. Sixty‐one percent of the patients received cranial neuroimaging. 8.2% had only cranial computed tomography (CT), 7.5% had cranial CT and cranial MRI, and 84.3% had only cranial MRI. 22.1% of the patients had abnormal cranial MRI findings. The rate of incidental non‐specific white matter changes detected in our study group was 23/527 (4.4%). Among the 23 patients, 12 (52.2%) were male and 11 (47.8%) were female. Fourteen (60.9%) had migraine without aura, 8 (34.8%) had tension‐type headache, and 1 (4.3%) had migraine with aura. Mean age of patients at the time of imaging was 12.1 ± 3.4 years (range 4.0‐16.0 years). All patients with non‐specific white matter changes on MRI showed normal psychomotor development, and there was no history of seizures or head trauma. The physical and neurological examinations of all patients were normal. The mean clinical follow‐up period of the patients was 16.8 ± 17.3 months (range 6‐80 months). No patients showed neurological deterioration during the follow up. The white matter lesions were supratentorial in all patients. The mean size of the lesions was 5.1 ± 4.5 mm (minimum, 2 mm; maximum, 24 mm). Repeated radiological evaluations were performed in 11 (47.8%) of the patients. No new white matter lesions were detected in control MRI during follow up. Conclusion: Non‐specific incidental white matter changes may be seen in children with headache. For normal clinical follow up, in the absence of evident benefits from repeated imaging studies, we suggest that repeated imaging studies are not warranted in every patient and should be tailored according to clinical course.